2010
DOI: 10.1177/0960327109360364
|View full text |Cite
|
Sign up to set email alerts
|

Catechol cytotoxicity in vitro: Induction of glioblastoma cell death by apoptosis

Abstract: The exposure to benzene is a public health problem. Although the most well-known effect of benzene is hematopoietic toxicity, there is little information about the benzene and its metabolites effects on the central nervous system (CNS). This study examined the toxic effects of 1,2-dihydroxybenzene (catechol), a benzene metabolite, to human glioblastoma GL-15 cells. GL-15 cell cultures were used as a model to provide more information about the toxic effects of aromatic compounds to the CNS. Catechol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Indeed, phenol at 1 mM did not cause an increase in phosphatidylserine exposure in K562 cells. Catechol has been demonstrated to induce apoptosis in glial cells, glioblastoma cells, neuroblastoma cells, glandular stomach cells, HL60 cells, and CD34+ progenitor cells (Moran et al, ; Hirose et al, ; Bironaite et al, ; Lima et al, ; de Oliveira et al, ; Mansoor et al, ). After exposure to hydroquinone, cell apoptosis occurred in various cells (Kerzic et al,; Shen et al,; Ibuki and Goto, ; Inayat‐Hussain et al, ; Rubio et al,; Yang et al, ; Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, phenol at 1 mM did not cause an increase in phosphatidylserine exposure in K562 cells. Catechol has been demonstrated to induce apoptosis in glial cells, glioblastoma cells, neuroblastoma cells, glandular stomach cells, HL60 cells, and CD34+ progenitor cells (Moran et al, ; Hirose et al, ; Bironaite et al, ; Lima et al, ; de Oliveira et al, ; Mansoor et al, ). After exposure to hydroquinone, cell apoptosis occurred in various cells (Kerzic et al,; Shen et al,; Ibuki and Goto, ; Inayat‐Hussain et al, ; Rubio et al,; Yang et al, ; Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that inhibition of erythroid differentiation played a role in benzene exposure‐induced erythropoietic depression. On the other hand, it has been reported that benzene metabolites, including phenol, catechol, hydroquinone, and 1,2,4‐benzenetriol, induced apoptosis in various types of cells (Moran et al, ; Bironaite et al, ; Inayat‐Hussain et al, ; Yamamoto et al, ; de Oliveira et al, ; Rubio et al, ; Yang et al, ; Lee et al, ) . It was suggested that benzene metabolites‐induced apoptosis should be involved in benzene‐induced erythropoietic depression.…”
Section: Introductionmentioning
confidence: 99%
“…Catechol is not toxic to glioblastoma cells at concentrations below 0.2 mM [30]; however, it induces a 44% increase in esophageal cell death at 35 µM [4], suggesting that it exhibits differential cytotoxicity that is cell type-dependent.…”
Section: Discussionmentioning
confidence: 96%
“…The cells were permeabilized in methanol at −20°C for 10 min and incubated with the primary antibody (rabbit polyclonal IgG anti GSTP1/2—Santa Cruz®, 1:500) for 1 h. Subsequently, cells were rinsed three times with PBS, incubated with the secondary antibody (Conjugated Alexa Fluor® 546 goat anti-rabbit IgG—Invitrogen®, 1:400) and finally observed by fluorescence microscopy (Olympus AX70 microscope—green filter). Nuclei were stained by the dye Hoechst 33258 (ex/em 340/510 nm) (Oliveira et al, 2010). For negative control, cells were incubated with only secondary antibody under the same conditions described above.…”
Section: Methodsmentioning
confidence: 99%